Peran Strategis Green Sukuk dalam Mendukung Pembangunan Berkelanjutan: Studi Berbasis Literatur Global 2021–2025 - Dio Firmansyah; Peni Haryanti (Journal of Economic and Business Advancement, 2025)
This study investigates the strategic role of Green Sukuk in supporting global sustainable development agendas during the 2021–2025 period through a systematic review of international literature. By synthesizing findings from peer-reviewed articles, institutional reports, and global regulatory guidelines, this research identifies Green Sukuk as a rapidly expanding Islamic financial instrument that bridges environmental objectives with Sharia-compliant investment principles. The analysis reveals that Green Sukuk contributes significantly to financing renewable energy, climate-resilience programs, waste management, and low-carbon infrastructure, particularly in emerging economies such as Indonesia, which has become one of the world’s leading issuers. The study highlights that transparency, external verification, and alignment with Environmental, Social, and Governance (ESG) indicators strengthen investor confidence and mitigate risks associated with greenwashing. Additionally, the integration of Maqasid al-Shariah principles reinforces the ethical foundations of Green Sukuk, positioning it as a dual-legitimacy instrument with financial and moral value. Overall, the findings demonstrate that Green Sukuk functions not only as a sustainable financing tool but also as a policy mechanism that accelerates green economic transition and broadens public participation through both institutional and retail investment models.